Kajian Kuat Cabut Tulangan Pada Beton Yang Diperkuat Sika Grout-215 - Suwarto Suwarto; Wasino Wasino (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2012)
Sika-215 Grout is ready grouting material that has multiple features have expanded properties and very easy in use, that is just simply add water with a specific ratio. Many application are already using this material for purposing of anchorage bolts, precast concrete connections, but more broadly-215 sika grout can be used for machine foundations, column base plates, foundation support a bridge, and so on. The purpose of this study to determine how many influence the shape and length of anchorage against strong pull between the anchor-reinforced concrete grout Sika 2l5. Specimens in this study a concrete cube 15x15x15 cm 2 for the strong pull and testing of concrete cylinders with a diameter of 15cm, a height of 30 cm for the characteristic compressive strength testing, the concrete mix design based on the K-225 at 28 days, while the iron anchor used is concrete screw diameter of 16 mm. The results showed that the long form of anchor and anchoring to the real effect of the strong pull Out force is generated. With a surface area of 225 cm2 test piece, grout Sika grouting material 215 provides a powerful pull an average of 6834 ton maximum length that occurs in the form of anchoring 14cm straight (type-a, and 6 cm diameter hole grouting.